Exploring the rheological and thermal behavior of cowpea protein concentrate: Impact of pH and concentration - Oliveira, Maria Mariana Garcia de [UNESP]; Fessori, Ana Gabriela Baroni Wicher [UNESP]; Huamaní-Meléndez, Víctor Justiniano [UNESP]; Mauro, Maria Aparecida [UNESP] (Elsevier, 2024)
This study confronts challenges from global population growth, focusing on protein supply strains and the environmental impact of traditional animal sources. Delving into unexplored territory, this study investigates the combined effects of pH, concentration, and temperature on the rheological and thermal properties of cowpea protein concentrate (CPC). Steady-state and oscillatory rheological tests, along with differential scanning calorimetric analysis, were conducted to unveil the behavior of CPC solutions. The results revealed sensitivity to protein concentration and shear rate, especially at higher concentrations (>10%), and pH emerged as a critical factor, significantly influencing shear stress and viscosity. The elastic and viscous components of alkaline CPC solutions exhibit weak gel behavior, influenced by both pH and frequency. Temperature-induced changes in viscosity and gelation highlight the interaction between thermal conditions and protein structures. The thermal cycle helps explain changes in molecular interactions induced by temperature, with pH playing a role in influencing gelatinization and denaturation. The denaturation temperature (Td) in the thermograms corresponds to vicilin fractions and emphasizes the prominence of denaturation and gelation at neutral pH, where Td was pH 7 > pH 9 > pH 11. Alkaline pH induced significant structural changes, resulting in a gelation onset temperature below the denaturation onset temperature. This study provides a deeper understanding into the rheological and thermal properties of CPC solutions, emphasizing the roles of concentration, pH, and temperature, useful for various steps of industrial processing, before and after thermal gelation. These findings are important for promoting the use of cowpea proteins in the food industry in response to the evolving needs of a growing global population.
Keywords: Apparent viscosity; Differential scanning calorimetry; Plant protein; Protein denaturation; Rheology